ESD - FUNCTIONAL CLOTHING - SCARLAT Razvan (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2016)
The functional clothing represents a sustainable development direction of in the field of technical textiles, a bridge between various activity domains, a solution to user’s complex requirements. The research and development potential in the field is supported by the new fibers/ yarns generation, the new technologies and the market niches, as well. Protective clothing is now a major part of textile classified under technical textile. Protective clothing refers to the garment and other fabric related items designed to protect the wearer from harsh environmental effects that results in injuries or death. The innovation, as a result of convergence processing technologies, consumer demands and what is viable on the market, defines the personal protective equipment field. In this article, we present the work of an ESD protective clothing development. Therefore, it has been applied a modern knitting technology, on 7E and 12E STOLL machines, using cotton and wool yarns as base yarn and conductive yarns for plaiting structures. Also, the optimal parameters establishment and the functional requirements are aspects of the research activity performed. The experimental models have been conducted in order to demonstrate the design concept used and choosing the optimal variant. The characterization of the developed experimental variants took into account the evaluation of physico-mechanical and electrical characteristics. From the electrical point of view, the variants have been mainly evaluated through “point to point” method in terms of electrical isolation efficiency dimensional changes analysis.